Destination Image, Sport Event Quality, and Behavioral Intentions: The Cases of Three World Sambo Championships. (September 2021) - Milovanović, Ivana; Matić, Radenko; Alexandris, Kostas; Maksimović, Nebojša; Milošević, Zoran; Drid, Patrik
This research tested the interactions among destination image, destination quality, sport event quality, and behavioral intentions in the context of small-scale sport events. The study included elite sambo athletes (N = 350) who participated in the World Sambo Championships, which were organized in Novi Sad (Serbia) in 2017 and 2018. The destination image was measured with the affective and cognitive dimensions, while the event quality was measured with the core, tangible and supporting dimensions. The results supported the measurement and structural models. They further indicated that the core aspect of the event quality directly influences participants' behavioral intentions, while the destination quality partially mediates the relationship between destination image and participant behavioral intentions. The event quality was shown to have a direct relationship with the development of destination loyalty. The theoretical and applied value of these results are discussed.